Zn(Ii)-Porphyrin-Squaraine Dyads as Potential Components for Dye-Sensitized Solar Cells: A Quantum Chemical Study of Optical and Charge Transport Properties - Cardenas-Jiron, G; Borges-Martinez, M; Montenegro-Pohlhammer, N (American Chemical Society, 2020)
In the present work, we theoretically investigate the push-pull effect in new dyads of chromophores formed by substituted Zn(II) porphyrin (P) and squaraine (SQ) that could be potential components of dye-sensitized solar cells (DSSCs). The effect of electron-donating moieties (amine, methoxy, and methyl) bound to porphyrin in meso-position C20 on the optical and charge transport properties of nine dyads (D1-D9) was studied, as well as the formation reaction of these. After a calibration procedure with 13 density functionals, the electronic spectra of the dyads were computed (TPSSh/def2-TZVP) with time-dependent density functional theory (TD-DFT). Dyads with amines (D5-D9) show a push effect denoted by the red-shifting of the Q-bands (up to 727 nm), while dyads with methyl or methoxy substituents (D1-D4) show no significative changes. Charge transfer bands computed with both TD-DFT and perturbative ΔSCF approaches preferably show a P → SQ transition, which indicates that porphyrin is a better electron-donating moiety (push effect), while squaraine is a better electron-withdrawing moiety (pull effect). Charge transport properties of the dyads calculated with the Keldysh nonequilibrium Green s function (NEGF) formalism show a similar trend, with the current shifting P → SQ more favorably for dyads with amine groups. The latter would be more convenient for DSSCs. Copyright © 2020 American Chemical Society.